Testing a system for monitoring the operation of hydraulic complexes at hydromechanized mines - V. Р. Drobadenko; А. L. Vilmis; О. А. Lukonina; К. S. Nekoz; I. N. Salakhov (Известия высших учебных заведений: Геология и разведка)
Background. An analysis of the process of hydraulic mining at mines found the absence or irregularity of monitoring of the main parameters of slurry transportation. These parameters include the flow rate and density of the slurry, which determine the hourly output in terms of the rock mass delivered from open pits for processing. This problem impedes regulation of the technological modes of the “open pit–processing plant” hydraulic complex.Aim. To increase the hourly output of the hydraulic complex operation, the stability of slurry transportation for beneficiation, as well as the extraction of the valuable component.Materials and methods. Variable pressure measurements were conducted using a hydrostatic densitometer; a Venturi tube flowmeter, including a converging calibration device; a flowmeter with a diverging anti-Venturi device, and a DK-25-40 chamber-type orifice plate. An Induction-51 electromagnetic flowmeter with an accuracy class of 1.5% was used as a calibration device.Results. The throughput of slurry transportation by the tested flowmeters was found to differ insignificantly in terms of the flow coefficient (about 0.97–0.98). However, the slurry flow rate in the anti-Venturi flowmeter minimizes the wear of the inner walls of the calibration part of the pressure tap. The accuracy of flow measurements depends on the constancy of the Venturi tube cross-section, which is subjected to wear during operation (a runtime of about 650 h and the technological resource in the tests of 110500 m3 ). Substantiation for the application of an anti-Venturi flowmeter is given. Local hydraulic resistances in the diffuser (diverging section) were determined, which mainly depend on such geometric characteristics as the divergence angle α, the divergence degree n, and the diffuser length Іd. The optimal values of geometric parameters were found to be as follows: α=5÷7° at Іd  =0.8÷1.5.Conclusion. According to the results of industrial testing of an anti-Venturi flowmeter at the flow rate of Q=2500 m3/h during several months of mining works, this device can be recommended for application as part of monitoring systems for slurry transportation modes. This device increases the equipment performance and the extraction degree of the valuable component.